Sphingosine Kinase 1 in Breast Cancer—A New Molecular Marker and a Therapy Target - Alshaker, Heba; Thrower, Hannah; Pchejetski, Dmitri (Frontiers in Oncology, 2020)
It is now well established that sphingosine kinase 1 (SK1) plays a significant role in breast cancer development, progression, and spread, whereas SK1 knockdown can reverse these processes. In breast cancer cells and tumours SK1 was shown to interact with various pathways involved in cell survival and chemoresistance, such as nuclear factor-kappa B (NFκB), Notch, Ras/MAPK, PKC and PI3K. SK1 is upregulated by oestrogen signalling which in turn confers cancer cells with resistance to tamoxifen. Sphingosine-1-phosphate (S1P) produced by SK1 has been linked to tumour invasion and metastasis. Both SK1 and S1P are closely linked to inflammation and adipokine signalling in breast cancer. In human tumours, high SK1 expression has been linked with poorer survival and prognosis. SK1 is upregulated in triple negative tumours and basal-like subtypes. It is often co-expressed with ERK-1/2, SFK, LYN, AKT and NFκB. Higher tumour SK1 mRNA levels were correlated with poor response to chemotherapy. This review summarises the up-to-date evidence and discusses the therapeutic potential for the SK1 inhibition in breast cancer with the emphasis on the mechanisms of chemoresistance and combination with other therapies such as gefitinib or docetaxel. We have outlined four key areas for future development, including tumour microenvironment, combination therapies and nanomedicine. We conclude that SK1 may have potential as a target for precision medicine, its high expression being a negative prognostic marker in ER-negative breast cancer, as well as a target for chemosensitisation therapy.